Seismic vulnerability and loss assessment of Vila Real de Santo António, Portugal: application of a novel method - Ortega, Javier (2022)
The city of Vila Real de Santo António (VRSA) was erected after the 1755 Lisbon earthquake following a Pombaline development similar to the well-known reconstruction of Lisbon downtown. It included seismic-resistant measures at an urban and architectural level, but most original buildings have nowadays been replaced or are highly altered. A research question arises whether or not and to what extent these alterations have compromised the seismic vulnerability of the historical city center. The paper presents the seismic vulnerability assessment of the historic city center of VRSA using a newly developed method: Seismic Assessment of the Vulnerability of Vernacular Architecture Structures (SAVVAS). The method proposes a numerical tool intended to estimate the seismic capacity of vernacular buildings using qualitative and simple quantitative data that can be rapidly obtained from visual inspections. The seismic vulnerability and loss assessment consider different scenarios, including the historical condition, and studies different retrofitting strategies. KEYWORDS: urban retrofitting strategies vernacular architecture